PENGARUH PENGELOLAAN KELAS OLEH GURU TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOM - Syaripah Rizky; Aminuyati Okianna; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This thesis is entitled "The Effect of Classroom Management by Teachers on Learning Outcomes in Economics Subjects in Class XI Accounting in SMK Mandiri Pontianak". The method used in this research is descriptive method in the form of a study of relationship studies. Data collection techniques in this study use indirect techniques and documentary study techniques. Meanwhile, to analyze the data the researcher used the SPSS version 16.0 statistical program. With the help of the SPSS version 16.0 application, the data analysis results were obtained which stated there was an influence between classroom management on student learning outcomes in Pontianak Independent Vocational School at 7.4% with a coefficient of determination of 0.271 and the level of interpretation of the relationship is low. Based on the SPSS output table in Appendix 19 with the title Model Summary, it can be determined the value of the correlation coefficient influence the availability of teachers in terms of competence on learning outcomes of 0.271 (R) with R Square 0.074, which is determined by the formula KD = R2 x 100% (KD = 0.074 x 100%) to 7.4%. Thus, the effect arising from the management is not dominant by only 7.4% and the rest is influenced by other influences outside this study. Keyword : Classroom Management, Learning Outcomes, Economic Subjects. PENDAHULUAN